Perovskite Metal–Oxide–Semiconductor Structures for Interface Characterization (Adv. Mater. Interfaces 20/2021). Issue 20 (22nd October 2021) - Cunha, José M. V.; Barreiros, M. Alexandra; Curado, Marco A.; Lopes, Tomás S.; Oliveira, Kevin; Oliveira, António J. N.; Barbosa, João R. S.; Vilanova, António; Brites, Maria João; Mascarenhas, João; Flandre, Denis; Silva, Ana G.; et al.
Abstract : Perovskite MOS Structures In article number 2101004, José M. V. Cunha and co‐workers demonstrate that AC measurements performed on metal–oxide–semiconductor devices (MOS) allow for the study of the density of interface defects and interface fixed oxide charges present in the electron transport layer/perovskite interface, allowing for the development of highly‐efficient perovskite solar cells, which have several applications, e.g., build‐integrated photovoltaics.